2018
DOI: 10.1159/000489310
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Self-Management: A Key to Better Health-Related Quality of Life in Patients with Diabetes

Abstract: Objective: The aims of this study were to assess health-related quality of life (HRQOL) among adult patients with diabetes attending primary health care diabetes clinics in Kuwait and to examine the factors associated with the HRQOL of patients with diabetes. Methods: This cross-sectional study was conducted among 503 patients with diabetes attending 26 primary health care diabetes clinics in Kuwait. A self- administered questionnaire on participants’ socio-demographic and clinical characteristics, in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
27
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 23 publications
4
27
0
5
Order By: Relevance
“…The variables that have been demonstrated to affect HRQOL in patients with DM are diabetes self-management (DSM), diabetes distress (DD), depression, selfefficacy, and family support [10,[14][15][16][17]. Although the predictors of HRQOL in patients with DM have been studied, it remains unclear whether they apply to both younger and older adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…The variables that have been demonstrated to affect HRQOL in patients with DM are diabetes self-management (DSM), diabetes distress (DD), depression, selfefficacy, and family support [10,[14][15][16][17]. Although the predictors of HRQOL in patients with DM have been studied, it remains unclear whether they apply to both younger and older adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…A study in Kuwait by Al-Khaledi 11 reported that diabetes self-management (DSM), gender, and diabetes complications were significant independent correlates to health-related quality of life. Another study conducted in King Saud Medical City, Riyadh, Saudi Arabia, 12 revealed positive associations between medication adherence and diabetes knowledge; self-management behaviors (glucose management and healthcare use) and diabetes knowledge; self-management behaviors (dietary control) and fasting blood glucose levels; and age and blood glucose levels (both fasting and HbA1c).…”
mentioning
confidence: 99%
“…So, because of the multifactorial reasoning of DSM and complexity of the relationship between DSM and various factors, having good DSM behaviors and improving them are challenging issues for healthcare providers and patients. Good compliance with DSM behaviors leads to better control of the disease, preventing or delaying diabetes-related complications, and promoting patients' quality of life [7,12,14].…”
Section: Discussionmentioning
confidence: 99%
“…A statistically significant negative correlation has been reported between diabetes self-management behaviors with HbA1c level [12]. Studies have shown that good DSM leads to improving metabolic control and quality of life in diabetes patients [13,14].…”
Section: Introductionmentioning
confidence: 99%